2010
DOI: 10.1080/03601231003613443
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the interaction between soil and antibiotics

Abstract: The aim of this study was to investigate the occurrence of tetracycline and sulfonamide antibiotics in 13 different soil samples collected from agricultural fields. As well as the antibiotic analysis 18 different physicochemical properties of the soil samples were determined in order to establish a relationship between the recovery rates of antibiotics from the samples and the characteristics of the samples that provide critical information for the reliability of an applied antibiotic analysis method. While th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…Previous studies demonstrated that antibiotic dissipation in soils is influenced by environmental factors, such as temperature, pH, and soil physicochemical properties, as well as the initial concentrations of antibiotics and their associated matrixes (Otker and Akmehmet-Balcioglu, 2005;Cengiz et al, 2010;Srinivasan and Sarmah, 2014). Chemical properties of the antibiotics can also influence their interactions with soil minerals and organic matter (Otker and Akmehmet-Balcioglu, 2005;Wegst-Uhrich et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that antibiotic dissipation in soils is influenced by environmental factors, such as temperature, pH, and soil physicochemical properties, as well as the initial concentrations of antibiotics and their associated matrixes (Otker and Akmehmet-Balcioglu, 2005;Cengiz et al, 2010;Srinivasan and Sarmah, 2014). Chemical properties of the antibiotics can also influence their interactions with soil minerals and organic matter (Otker and Akmehmet-Balcioglu, 2005;Wegst-Uhrich et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Antibiyotiklerin suda, atıksuda, toprakta ve çamurda kirletici olarak saptanması ve bu matrikslerde giderimlerini konu alan çalışmalar son yıllarda bilimsel literatürde önem kazanmıştır [19][20][21][22][23][24]. Düşük konsantrasyonlardaki antibiyotiklerin mikroorganizmalarda direnç gelişimine neden olduğu uzun yıllardır bilinmektedir.…”
Section: Kirletici Türleri Ve çEvresel Etkileriunclassified
“…It has been clearly shown that the number of antibiotic resistance genes increases in soil after application of manure sourced from a farm operation with low or regular use of antibiotics (Schmitt et al, 2006;Cengiz et al, 2010). In addition to already-resistant bacteria, manure can also contain antibiotics that lead to the development of resistance in the environment, and indigenous soil bacteria can create an undesirable reservoir for the spread of antibiotic resistance (Kummerer, 2004).…”
Section: Introductionmentioning
confidence: 99%